2014
DOI: 10.1007/s10853-014-8481-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun green fibres from lignin and chitosan: a novel polycomplexation process for the production of lignin-based fibres

Abstract: Novel lignin-chitosan polyelectrolyte fibres were produced through a reactive electrospinning process. Polyelectrolyte formation between the anionic lignin and cationic chitosan was controlled through the pH of the solution. Through manipulating the polyelectrolyte complex formation, fibres could be effectively produced from two biopolymers, which are normally very difficult to electrospin on their own. Though minimal amounts of the petroleum-derived polyethylene oxide were introduced into the solution to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Collected electrospun nanofiber morphologies suggested that above 80% of lignin in PEO solution makes the electrospinning process unstable, and below this percentage nanofibers collected were stable and smooth, and at 80% of lignin in PEO solution, fiber diameter obtained was 150 nm. Schreiber et al, (2014) [197] fabricated electrospun nanofibers from anionic sodium carbonate lignin (ASCL), cationic chitosan (CC), and PEO via polyelectrolyte complex formation under a controlled pH and showed a mixed biopolymer nanofiber production, which is otherwise difficult to fabricate. Solutions were prepared with different ASCL, CC, and PEO concentration in w/v %, namely-0.6% PEO, 1.5% chitosan and 1.5, 2.0, 2.5, or 3.0% ASCL.…”
Section: Pure Ligninmentioning
confidence: 99%
“…Collected electrospun nanofiber morphologies suggested that above 80% of lignin in PEO solution makes the electrospinning process unstable, and below this percentage nanofibers collected were stable and smooth, and at 80% of lignin in PEO solution, fiber diameter obtained was 150 nm. Schreiber et al, (2014) [197] fabricated electrospun nanofibers from anionic sodium carbonate lignin (ASCL), cationic chitosan (CC), and PEO via polyelectrolyte complex formation under a controlled pH and showed a mixed biopolymer nanofiber production, which is otherwise difficult to fabricate. Solutions were prepared with different ASCL, CC, and PEO concentration in w/v %, namely-0.6% PEO, 1.5% chitosan and 1.5, 2.0, 2.5, or 3.0% ASCL.…”
Section: Pure Ligninmentioning
confidence: 99%
“…In addition to that lignin has been used for the synthesis of various types of carbon materials including activate carbon, carbon black and carbon fibers. Recent developments in lignin based carbon materials are the fabrication of electrospun carbon nanofibers and other carbon based particulate nanostructures for various technological applications . However, the nanofabrication techniques have not been investigated to a great extent.…”
Section: Introductionmentioning
confidence: 99%
“…The electrospinnability of lignin was significantly enhanced by the use of easily electrospun synthetic polymers. 9,11,12 However, as Dallmeyer et al. 9 and Schreiber et al.…”
mentioning
confidence: 95%
“…The electrospinnability of lignin was significantly enhanced by the use of easily electrospun synthetic polymers. 9,11,12 However, as Dallmeyer et al 9 and Schreiber et al 12 fabricated lignin-based nanocomposite fibers to produce precursors for carbon fibers, they focused on ways to control the diameters and morphology of the resulting fibers in order to yield highquality carbon fibers. In other words, there has been a scarcity of research on the functionalities of ligninbased nanocomposite fibers for use as final products.…”
mentioning
confidence: 99%